Quality of Life and Life Satisfaction of People with Disabilities during Forced Social Distancing and Home Confinement Derived from the COVID-19 Pandemic - Chykhantsova , Olena; Kievišienė , Justina; Baranauskienė, Ingrida; Agostinis-Sobrinho, Cesar (Special Education, 2022)
This study aimed to analyze the quality of life and life satisfaction of people with disabilities in quarantine due to the COVID-19 pandemic in Ukraine and Lithuania. There were total 546 participants aged 16-84 years from Lithuania and Ukraine. The respondents completed the authors’ questionnaire and the Subjective Happiness Scale to measure quality of life, subjective happiness, and life satisfaction. Pearson’s correlation coefficient was used to assess the associations between quality of life, subjective happiness, and life satisfaction. The results demonstrate the interrelation between the constructs measured, when subjectively evaluated quality of life during quarantine was associated with satisfaction within various life spheres, and moderately associated with subjective happiness. In conclusion, our study showed the interdependence between quality of life, subjective happiness and life satisfaction, allowing manipulation of separate components to induce change in other not only in scientific rapport, but also in physical and mental health orientated preventative actions to improve the well-being for people with disabilities